Adenoid cystic carcinoma: An unusual presentation - Pushpanjali, M (Medknow Publications & Media Pvt Ltd, 2014)
The adenoid cystic carcinoma is a relatively rare epithelial tumor of the major and minor salivary glands, accounting for about 1% of all malignant tumor of the oral and maxillofacial regions. Peak incidence occurs between the 5(th) and 6(th) decades of life. The clinical and pathological findings typical of this tumor include slow growth, peri-neural invasion, multiple local recurrences and distant metastasis. Herein, we report a case of adenoid cystic carcinoma of oropharynx with unusual clinical presentation. The diagnosis of this case and importance of cytology in diagnosing such cases is discussed.